(untitled) (INNOVATIVE ECONOMY, 2023)
Putsenteilo P.R. THE CONCEPT OF SMART GRID: TECHNOLOGICAL, ORGANIZATIONAL AND ECONOMIC ASPECTS OF THE DEVELOPMENT OF THE ENERGY SECTOR Purpose. The aim of the article is to substantiate the concept of Smart Grid application from the point of view of technological, organizational and economic aspects of development in the energy sector, outlining the features of their use in modern conditions and in the future. Methodology of research. The methodological basis of the research is the dialectical method of scientific knowledge. General scientific and special methods were used in the research process, in particular analysis and synthesis, dialectical – to determine the initial conditions and content of the Smart Grid; analytical – when processing literary and Internet sources; causal – to determine the dynamics of Smart Grid technology development in the world; abstract and logical – for outlining the main directions of operation of Smart Grid technologies in the field of energy, forming conclusions and proposals. Findings. Current and prospective Smart Grid technologies in the energy industry are summarized. The need for intellectualization of the electric power industry through the formation of a digital electric power network is substantiated. Measures to create a unified technical and informational infrastructure for electricity producers and consumers thanks to the Smart Grid concept have been determined. An assessment of the dynamics of investment in Smart Grid technologies in the world was carried out, the volume of the world market of Smart Grid technologies was determined, and the income of the world market of electricity supply and management was analysed. Originality. Measures to increase the introduction of Smart Grid in the energy sector are substantiated, which will make it possible to strengthen Ukraine’s energy independence and contribute to the introduction of energy-saving technologies. The main vectors of the development of the electric power industry using the Smart Grid concept are proposed: design and use of modernized, new and breakthrough (critical) technologies; development of new energy management systems based on the principles of information interaction of energy facilities; involvement of individual and collective consumers in energy consumption management. Practical value. The substantiated research results can be used for the formation of innovative Smart Grid technologies in the field of energy security of Ukraine. Key words: Smart Grid, intelligent network, energy, energy security, energy supply, renewable energy sources.